2021
DOI: 10.3390/life11070681
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Thermal Comfort during Skin Cooling and Heating

Abstract: Due to the static and dynamic activity of the skin temperature sensors, the cutaneous thermal afferent information is dependent on the rate and direction of the temperature change, which would suggest different perceptions of temperature and of thermal comfort during skin heating and cooling. This hypothesis was tested in the present study. Subjects (N = 12; 6 females and 6 males) donned a water-perfused suit (WPS) in which the temperature was varied in a saw-tooth manner in the range from 27 to 42 °C. The rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Mekjavic and colleagues presented a strong correlation between the perception of thermal comfort and the behavioural regulation of thermal comfort, which was not proved by previous studies [ 21 ]. Moreover, they showed that gender and age are two important factors that explain thermal comfort variability [ 21 ]. These results are important to consider in future thermal comfort evaluations.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Mekjavic and colleagues presented a strong correlation between the perception of thermal comfort and the behavioural regulation of thermal comfort, which was not proved by previous studies [ 21 ]. Moreover, they showed that gender and age are two important factors that explain thermal comfort variability [ 21 ]. These results are important to consider in future thermal comfort evaluations.…”
mentioning
confidence: 64%
“…Finally, assessing thermal comfort is of great interest for estimating the conditions where most humans would feel comfortable in an everyday environment [ 21 ]. Mekjavic and colleagues presented a strong correlation between the perception of thermal comfort and the behavioural regulation of thermal comfort, which was not proved by previous studies [ 21 ]. Moreover, they showed that gender and age are two important factors that explain thermal comfort variability [ 21 ].…”
mentioning
confidence: 99%
“…Perceived thermal sensation ( Brazaitis et al, 2014 ), perceived thermal discomfort ( Mekjavic et al, 2021 ), and blood pressure (BP) were measured at the end of the baseline and exercise, at the onset and throughout TWI (every 5 min), and post TWI. The thermal sensation scale ranged from 1 (very cold) to 9 (very hot), with 5 being neutral.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, neurophysiological studies have gained large popularity to complement psychophysical studies (or subjective assessment), as it is sometimes difficult to assess the effect of the external stimulus using psychophysical scales [260]. The technique involves the observation of the electrical and chemical activity of the human brain in response to external stimuli [275,276], which are recorded using various advanced techniques, such as electroencephalography, transcranial magnetic stimulation, positron emission tomography, and functional magnetic resonance imaging. The cutaneous thermal and wetness cues originating at the thermal and mechanoreceptors of the human skin travel through four regions to generate a neural response [2,260].…”
Section: Objective Assessmentmentioning
confidence: 99%